Performance evaluation of primary user and secondary user based on CSMA protocol in CRSN - Ying LIU; Li ZHENG; Yuansong LI (Dianxin kexue)
For the problem of uncertainty owing to the highly variable physical layer characteristics in cognitive radio sensor networks（CRSN），two fundamental performance metrics（bandwidth and delay）were formulated and the performance of medium access control protocol based on CSMA was analyzed. Firstly，CSMA algorithm was used to estimate potential bandwidth of secondary user under the given PU traffic model. Then，aggregated bandwidth of multiple SU simultaneous transmitting within different business channels was derived. Finally，the priority queue model M/G/C was used to analyze the delay of MAC. Performance analysis shows that dedicating a common control channel for SU enhances their aggregated bandwidth approximately five times and the packet delay reduces significantly through the possibility of concurrent transmissions on different traffic channels.